Fluorescence-based, high-throughput DNA polymerase assay - Yu, Liming (BioTechniques, 2002)
The commonly used DNA polymerase assay is based on the detection of incorporated radiolabeled nucleotides in a DNA elongation reaction. It is laborious, radioactive, and can be highly variable. Here we report a nonradioactive fluorescence-based assay. The method consists of Cydye-labeled nucleotides, biotinylated primer, and a streptavidin-coated microplate. The assay is found to have sensitivity and dynamic range comparable to the classical radioactive method. Moreover, it has the advantages of being simple, stable, nonradioactive, and suitable for high-throughput applications. We have also found that, to ensure efficient measurement of the enzyme activity, the template DNA used in this method should have a sequence that avoids the incorporation of the fluorescence-labeled nucleotide in a consecutive way